The effect of the project citizen model on students’ critical thinking skills and communication competence - Ranti Ranti (Science Center Group, 2026)
Background: Civic education requires instructional approaches that foster students’ critical thinking skills and communication competence in order to prepare them for active democratic participation. The Project Citizen model offers a structured civic inquiry framework that integrates problem identification, policy analysis, and public presentation within classroom practice. Objective: This study aimed to examine the effect of the Project Citizen model on students’ critical thinking skills and communication competence in Pancasila Education at the secondary school level. Methods: A quasi-experimental design with a non-equivalent control group pretest–posttest format was employed. Sixty-four students were divided into an experimental group receiving Project Citizen instruction and a control group receiving conventional instruction. Data were collected using an essay-based critical thinking test and a performance-based communication rubric. Descriptive and inferential statistical analyses, including paired and independent samples t-tests, were conducted to determine differences within and between groups. Results: The findings revealed significant improvements in both critical thinking skills and communication competence among students in the experimental group compared to those in the control group. The experimental group demonstrated substantially higher mean gain scores in analytical reasoning, argument development, and presentation performance. The results indicate that structured civic project activities positively influence higher-order cognitive and communicative outcomes. Conclusion: The Project Citizen model effectively enhances students’ critical thinking skills and communication competence in Pancasila Education. The integration of civic inquiry, collaborative investigation, and public presentation provides a meaningful pedagogical framework aligned with contemporary curriculum demands and democratic education objectives.